Climate Policy and Ancillary Benefits: A Survey and Integration into the Modelling of International Negotiations on Climate Change - Karen Pittel; Dirk T. G. Rübbelke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Currently informal and formal international negotiations on climate change take place in an intensive way since the Kyoto Protocol expires already in 2012. A post-Kyoto regulation to combat global warming is not yet stipulated. Due to rapidly increasing greenhouse gas emission levels, industrialized countries urge major polluters from the developing world like China and India to participate in a future agreement. Whether these developing countries will do so, depends on the prevailing incentives to participate in international climate protection efforts. This paper identifies ancillary benefits of climate policy to provide important incentives to attend a new international protocol and to positively affect the likelihood of accomplishing a post-Kyoto agreement which includes commitments of developing countries.
Keywords: 330; ancillary benefits; climate change; international negotiations; chicken game; Klimaschutz; Verhandlungen; Nichtkooperatives Spiel; Kosten-Nutzen-Analyse; Theorie; Welt